Etnografia Wajãpi/AP do processo saúde-doença: um enfoque odontológico - Tiago Araujo Coelho de Souza (2005)
This study had as objective describes some aspects of the social and cultural representations of the Wajãpi/AP people and your appropriation process concerning the information in oral health. Was developed an ethnographical qualitative research where interviews, observations and annotations was used to know the conception of health and disease of Wajãpi/AP people. Also this study looked for try to identify the habits and the transformations in the Wajãpi alimentation along the contact with the national society. The results show that the contact process with the national society introduced the practice of the wage payment and with that the compromising with the biomedical speech; the change in the feeding of the population Wajãpi doesn't come from the biological need and nor of alimentary shortage, but of the obtaining of differentiated status produced by the own politics of the wage payment. In conclusion the mythical narratives and your interface with the oral health show that the cosmology doesn't explain the etiology of the health disease oral process, but it guarantees the entail relationship with the community, through the sensibility of the oral health team and the construction of instruments, culturally, differentiated. And, finally, there are evidences of questions about the oral health for the Wajãpi people this fact guarantees to us that this people are learning to aim at a new practice of oral health.